2023
DOI: 10.1055/a-2187-0645
|View full text |Cite
|
Sign up to set email alerts
|

Are NETs a Novel, Exciting, Thrombosis Risk Marker?

Guozheng Wang,
Simon Timothy Abrams,
Cheng-Hock Toh

Abstract: No Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…However, it remains uncertain whether NETs play a causal role in initiating thrombosis or are merely associated with thrombotic events. 70 Risk of bleeding was sought by Lahu et al 71 who identified an association with soluble glycoprotein VI levels but no increased risk of ischemic events in patients undergoing elective percutaneous coronary intervention. This identifies soluble glycoprotein VI as a potential biomarker that warrants deeper investigation to assess its viability as a tool for personalized patient care.…”
Section: Editors' Choice 83mentioning
confidence: 99%
“…However, it remains uncertain whether NETs play a causal role in initiating thrombosis or are merely associated with thrombotic events. 70 Risk of bleeding was sought by Lahu et al 71 who identified an association with soluble glycoprotein VI levels but no increased risk of ischemic events in patients undergoing elective percutaneous coronary intervention. This identifies soluble glycoprotein VI as a potential biomarker that warrants deeper investigation to assess its viability as a tool for personalized patient care.…”
Section: Editors' Choice 83mentioning
confidence: 99%